Searching for the roots of natural language: intentional communication among non-human primates - Kwiatek, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
Where should we seek the roots of natural language? Common sense suggests that human language should have somehow evolved from primitive vocal communication, which is also, to some extent, present among other animals, especially since primary humans mean of communication is speech. Some biological and psychological evidences, however, both from observation and experiments, indicate that for the missing evolutionary link between human language and animal (apes) communication one should take chimpanzee gestural communication, the only undoubtedly intentional non-human mean of communication.In this paper, I present the evidences for the aforementioned theory and draw some conclusions regarding the issue of two “sources” of language – biological and cultural evolution.